2021
DOI: 10.1016/j.stemcr.2021.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Defective autophagy and increased apoptosis contribute toward the pathogenesis of FKRP-associated muscular dystrophies

Abstract: Fukutin-related protein (FKRP) is a glycosyltransferase involved in glycosylation of alpha-dystroglycan (a-DG). Mutations in FKRP are associated with muscular dystrophies (MD) ranging from limb-girdle LGMDR9 to Walker-Warburg Syndrome (WWS), a severe type of congenital MD. Although hypoglycosylation of a-DG is the main hallmark of this group of diseases, a full understanding of the underlying pathophysiology is still missing. Here, we investigated molecular mechanisms impaired by FKRP mutations in pluripotent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…DMD 1023 and DMD 1003 iDRM also differentiated into multi-nucleated myotubes with near-typical myogenic index and myotube width. These results are similar to previous studies that have shown relatively unimpaired fusion in human iPSC–derived myoblasts from DMD ( Caputo et al, 2020 ) or LGMDR9 ( Ortiz-Cordero et al, 2021 ) patients. However, striations in DMD 1023 and DMD 1003 myotubes were qualitatively impaired relative to healthy 1001 myotubes.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…DMD 1023 and DMD 1003 iDRM also differentiated into multi-nucleated myotubes with near-typical myogenic index and myotube width. These results are similar to previous studies that have shown relatively unimpaired fusion in human iPSC–derived myoblasts from DMD ( Caputo et al, 2020 ) or LGMDR9 ( Ortiz-Cordero et al, 2021 ) patients. However, striations in DMD 1023 and DMD 1003 myotubes were qualitatively impaired relative to healthy 1001 myotubes.…”
Section: Resultssupporting
confidence: 92%
“…Similar issues related to myofibril immaturity have routinely been observed in myotubes derived from a variety of reprogrammed ( Boularaoui et al, 2018 ) and iPSC-derived myoblasts ( Lainé et al, 2018 ; Rao et al, 2018 ) and likely reduce the baseline and drug-induced differences in the phenotypes of healthy and diseased cells. Overall, the maturity of iDRM-derived myotubes observed in this study was similar or weaker than iPSC-derived myotubes ( Caputo et al, 2020 ; Ortiz-Cordero et al, 2021 ). Of note, however, iDRMs require less time, cost, and expertise to generate compared to iPSC-derived myoblasts, which may be especially beneficial for generating patient-specific muscle tissues in time-sensitive or resource-limited settings.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…In addition, a recent study using induced pluripotent stem (iPS) cells derived from FKRP-deficient LGMD2I or WWS patients revealed decreased autophagy and increased apoptosis in myotubes, indicating that alterations in cell homeostasis may be involved in DGpathy pathogenesis [ 53 ]. Effective biomarkers of DGpathy, including miRNA and lncRNA, have not been established to date.…”
Section: Pathological Mechanism Of Dgpathymentioning
confidence: 99%